METAPHORS OF WAK UTEH’S SONGS - Deby Ana; I Wy Dirgeyasa; Morada Tetty (LINGUISTICA, 2019)
This study dealt with metaphors of Wak Uteh’s Songs in Tanjungbalai. The objectives of the study were to investigate the types of metaphors and the cultural meaning of metaphors in wak uteh’s songs in Tanjungbalai. This study was conducted by using descriptive qualitative method. This data of this study was words, phrases, and utterances that contained metaphors in Wak Uteh’s Songs in Tanjungbalai. The source of data were lyrics of 10 songs of Wak Uteh’s songs.  The data were selected by using random sampling system. For collecting data, this study used the method of documentary technique. The instrument of this study is documentary sheet. The findings showed that there were four types of Metaphors used in Wak Uteh’s Songs consecutively, Synaesthetic Metaphors (4%), Anthropomorphic (13%), Animal (20%), and Concrete to Abstract (63%). The cultural meanings of the metaphors found in the lyrics of Wak uteh’s songs were literary ones over all about the conditions of social life, economy, and culture from Tanjungbalai Malay life in coastal areas. For example in Anthropomorphic Metaphor is “ambil lah duet seringgit puntong, untuk mamboli kain pandukong (silaule, line 11) as the meaning in the cultural meaning is “Taking a piece of dollar for buying a sling”. So, in this lyric told about the parents ordered someone to take the enough money to buy a sling, Ringgit was a monetary unit that was used by Malay people in Tanjungbalai in long time. Keywords: Metaphors, Tanjungbalai, Wak Uteh’s Songs